2022
DOI: 10.4103/ija.ija_257_21
|View full text |Cite
|
Sign up to set email alerts
|

Serratus anterior plane block and erector spinae plane block in postoperative analgesia in thoracotomy: A randomised controlled study

Abstract: Background and Aims: Managing pain after thoracic surgery is crucial and the traditional methods have many adverse effects. We aimed to evaluate serratus anterior plane block (SAPB) and erector spinae plane block (ESPB) in acute pain control in thoracic cancer surgeries. Methods: This randomised controlled, triple-blind study was performed on 90 patients, between 18 and 70 years old, scheduled for elective thoracic cancer surgery. Patients were allocated into three equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…In accordance, Hassan and Wadod (14) , have illustrated Both the ESBP and SAPB groups consumed considerably less postoperative morphine than the control group [ESPB (8.52 ±4.29 mg) SAPB (19.57 ±7.63 mg) control (36.37 ±8.27 mg)] (p <0.001).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In accordance, Hassan and Wadod (14) , have illustrated Both the ESBP and SAPB groups consumed considerably less postoperative morphine than the control group [ESPB (8.52 ±4.29 mg) SAPB (19.57 ±7.63 mg) control (36.37 ±8.27 mg)] (p <0.001).…”
Section: Discussionsupporting
confidence: 65%
“…Hassan and Wadod (14) have demonstrated that Scale of numerical ratings At rest, the pain levels were comparable between the groups, but after 30 minutes, two hours, and four hours of coughing, the pain scores in the ESPB and SAPB groups were considerably lower than those in the control group. At 8, 12, and 24 hours, there was no longer much of a difference between the control and SAPB groups, but the ESPB group still had the smallest difference.…”
Section: Discussionmentioning
confidence: 91%
“…Among the included articles, ve studies were judged as having a low risk of bias [23][24][25][26]27]. Two studies were judged as having an unclear risk of bias [29,30], and four studies were judged as having a high risk of bias [28, [31][32][33].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…Ten studies reported opioid consumption 24 h postoperatively in patients undergoing thoracic or breast surgery with ESPB and SAPB [23][24][25][26][27][28][29][30][31][32]. Meta-analysis revealed that ESPB signi cantly reduced 24-hour opioid consumption compared with SAPB (SMD: -0.76; 95% CI: -1.29 to -0.24; P < 0.01; I 2 = 88%) (Fig.…”
Section: -Hour Postoperative Opioid Consumptionmentioning
confidence: 99%
See 1 more Smart Citation